2022
DOI: 10.33192/smj.2022.52
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Comparative Study of Submerge vs. Non- Submerg Saturated Salt Solution Human Cadavers Embalming Method by Gross, Histological, and Microbiological Evaluation

Abstract: Objective: To investigate and develop the saturated salt embalming method and evaluate the cadavers.Materials and Methods: Eight cadavers were embalmed with a saturated salt solution (SSS) by submerged (SG, N=2) and non-submerged (NSG, N=6), then evaluated by gross dissection, which compared to living humans, fresh and Thiel’s cadavers. The histological evaluation was compared to textbook pictures. The assessments were recorded on a Likert scale from 0 (no resemblance) to 5 (most resemblance). Pre-and post-emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The covers of the dissection tables were opened 24 h per day for 2 weeks before perineum measurement (Durongphan et al 2020 ). This finding is consistent with our institution’s pilot study, and Tanaka et al found that opening the cadaver covers released formaldehyde vapor that had been trapped (Durongphan 2019 ; Tanaka et al 2003 ). In this study, the opening of the 24-h table covers throughout the academic year, together with floor plan redesign, lowered the mean S-level by 64.18% from 1.34 ± 0.71 ppm in 2018 to 0.48 ± 0.26 ppm in 2019 and the mean R-level (0.17 ± 0.09 ppm) decreased 70.18% from 2018 (0.57 ± 0.27 ppm).…”
Section: Resultssupporting
confidence: 90%
“…The covers of the dissection tables were opened 24 h per day for 2 weeks before perineum measurement (Durongphan et al 2020 ). This finding is consistent with our institution’s pilot study, and Tanaka et al found that opening the cadaver covers released formaldehyde vapor that had been trapped (Durongphan 2019 ; Tanaka et al 2003 ). In this study, the opening of the 24-h table covers throughout the academic year, together with floor plan redesign, lowered the mean S-level by 64.18% from 1.34 ± 0.71 ppm in 2018 to 0.48 ± 0.26 ppm in 2019 and the mean R-level (0.17 ± 0.09 ppm) decreased 70.18% from 2018 (0.57 ± 0.27 ppm).…”
Section: Resultssupporting
confidence: 90%